Optimizing thermal energy storage using multi-walled carbon nano tube infused polyethylene glycol composites: An experimental and simulation study - Yadav, Aman; Mahendran, Samykano; Kalidasan, B.; Sharma, Kamal; Pandey, A. K. (Elsevier, 2025)
Highly stable phase change materials with superior thermal properties and reliability are of utmost need for waste heat recovery applications. Due to low supercooling, non-corrosivity, and low phase separation, organic phase change materials are preferred for thermal energy storage over inorganic phase change materials. Despite their other advantages, the limited heat conductivity of organic phase change materials limits their practical use in thermal energy storage. Therefore, current research focuses on developing nano-enhanced organic phase change materials by dispersing one-dimensional thread-shaped multi-wall carbon nanotubes with different weight percentages to improve the thermal properties of the base PEG-1000 PCM. The two-step method was adopted to develop phase change material composites to establish an improved thermal network, resulting in improved thermal conductivity. An ongoing study evaluated structural stability, chemical stability, thermal property, optical absorptivity, transmissivity, and thermal reliability of the formulated nano-enhanced phase change material composites. The results demonstrated that the highest thermal conductivity of nanocomposite was improved by 104.2 % at 0.7 wt% multiwall carbon nanotube. The composite’s optimum latent heat and melting point were 41.5 ◦C & 140 J/g, respectively. Additionally, the composite retained its thermal and chemical performance after being subjected to 500 thermal cyclic studies. Subsequently, a heat transfer simulation study is conducted to exhibit the effect of higher thermal conductivity of newly formulated nanocomposites for heat transfer compared to base PCM using 2-D energy simulation software.